Elucidation the role of Co-MOF on hematite for boosting the photoelectrochemical performance toward water oxidation. (19th April 2023) - Cai, Jiajia; Tang, Xiangxuan; Zhong, Shiming; Li, Yongjun; Wang, Yiyang; Liao, Zhi; Wang, Jianmin; Mao, Keke; Xie, Qian
Abstract: Developing an efficient photoanode to convert solar energy into hydrogen fuel confronts big challenges owing to the sluggish water oxidation kinetics. Herein, we proposed a feasible method to coat Co-based metal-organic framework (Co-MOF) on Ti doped α-Fe2 O3 and revealed its functions on the oxygen evolution reaction (OER) and photoelectrochemical (PEC) water oxidation. The Co-MOF/Ti–Fe2 O3 showed a photocurrent density of 1.01 mA/cm 2 (1.23VRHE ) with a low turn-on voltage (Von ) of 0.80 VRHE . The significant improvement of photocurrent density which was ca. 3 times higher than the pristine Fe2 O3, was contributed by the improved charge separation efficiency on the surface rather than in the bulk. And this was validated by the increased trapping capacitance (Ctrap ) and reduced charge transport resistance (Rct ). Additionally, the low Von was attributable to the compromise of introduced surface states and the catalytic effect of the Co-MOF. In this work, we discovered the Co-MOF not only offered catalysis sites for OER, but shed light on its influence on the overall PEC water oxidation, and led to an in-depth understanding of cocatalysts on the PEC water splitting. Highlights: Co-MOF coated Ti-oped Fe2 O3 is successfully prepared by a facile two-step method. Photocurrent density significantly increases by 3 times and reaches 1.01 mA/cm 2 . Co-MOF shows excellent oxygen evolution kinetics. The Co-MOF would introduce the new surface states and lower the photovoltage. Co-MOF has little effect or deteriorates the charge separation efficiency in bulk.